2018
DOI: 10.1002/arch.21468
|View full text |Cite
|
Sign up to set email alerts
|

Cellular energy metabolism maintains young status in old queen honey bees (Apis mellifera)

Abstract: Trophocytes and oenocytes of queen honey bees are used in studies of cellular longevity, but their cellular energy metabolism with age is poorly understood. In this study, the molecules involved in cellular energy metabolism were evaluated in the trophocytes and oenocytes of young and old queen bees. The findings indicated that there were no significant differences between young and old queen bees in β-oxidation, glycolysis, and protein synthesis. These results indicate that the cellular energy metabolism of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…A. mellifera is a unique model system for aging and longevity studies. As a complete metamorphosis insect, the entire developmental period includes the egg, larva (age 1–7), pupa, and adult stages ( Lu et al, 2018 ). Studies on A. mellifera showed that the transcriptional expression levels of GS were particularly high in the 4th and 7th instar larvae, whereas the relative expression level of GP was lower in the 6th instar and newly emerged adults ( Łopieńska-Biernat et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A. mellifera is a unique model system for aging and longevity studies. As a complete metamorphosis insect, the entire developmental period includes the egg, larva (age 1–7), pupa, and adult stages ( Lu et al, 2018 ). Studies on A. mellifera showed that the transcriptional expression levels of GS were particularly high in the 4th and 7th instar larvae, whereas the relative expression level of GP was lower in the 6th instar and newly emerged adults ( Łopieńska-Biernat et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Insects have diverse energy metabolism pathways, including fatty acid metabolism, carbohydrate metabolism, the TCA cycle and oxidative phosphorylation [ 33 , 34 , 35 ]. In this study, we show that the related genes of SBPH oxidative phosphorylation pathway and the TCA cycle may affect RSV infection.…”
Section: Discussionmentioning
confidence: 99%